2017
DOI: 10.1016/j.actbio.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Promoting bioengineered tooth innervation using nanostructured and hybrid scaffolds

Abstract: Tooth innervation is essential for their function and protection and this can be promoted in vivo using polymeric scaffolds functionalized with immunosuppressive drug-loaded nanoparticles. Immunosuppressive therapy using biodegradable nanoparticles loaded with Cyclosporine A was found to accelerate the innervation of bioengineered teeth after two weeks of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…GFAP staining was associated with axons as seen after double‐staining using anti‐NF200 and anti‐GFAP antibodies (Figure e, enlargement, white arrowheads). In conditions where MTP‐NRP1 was injected, GFAP‐positive cells colocalized with NF200 positive axons as already described in immunosuppressive conditions (Kuchler‐Bopp et al, ). Growth cones labeled for GAP‐43 (Figure f) were present in the dental pulp, some of which were associated with blood vessels (Figure f, enlargement, white arrows).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…GFAP staining was associated with axons as seen after double‐staining using anti‐NF200 and anti‐GFAP antibodies (Figure e, enlargement, white arrowheads). In conditions where MTP‐NRP1 was injected, GFAP‐positive cells colocalized with NF200 positive axons as already described in immunosuppressive conditions (Kuchler‐Bopp et al, ). Growth cones labeled for GAP‐43 (Figure f) were present in the dental pulp, some of which were associated with blood vessels (Figure f, enlargement, white arrows).…”
Section: Resultssupporting
confidence: 69%
“…This approach may represent an alternative to our previous results, based on immunosuppressive conditions, showing that 91.5% of teeth obtained after 2 weeks of implantation in ICR mice treated with cyclosporine A (CsA) were innervated (Kökten, Bécavin, et al, ). Using another strategy, we showed that 88.4% of the teeth regenerated on (PLL/PLGA/CsA) 5 scaffolds contained peripheral axons coming from the TG that colonized the dental pulp up to the odontoblastic layer (Kuchler‐Bopp et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments using artificial products, such as dentures, crowns, bridges or oral implants, can recover tooth function, but there are no biological treatments for teeth. Physiological reconstruction is desirable for a tooth with a partial defect [14]. It may be difficult in vitro to regenerate the whole tooth consisting of dentine, including dental pulp, cementum and enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Obtener una óptima inervación del biodiente es otro reto a conseguir, lo cual ha sido ya evidenciado con el modelo de germen de órganos (3), así como en estudios de membrana de policaprolactona funcionalizada con factor de crecimiento neural (57,58). Esta inervación del biodiente permitiría la percepción neuronal ante estímulos nocivos y fisiológicos (51).…”
Section: Desafíos Y Perspectivas Futuras En La Elaboración De Un Biodunclassified